Linear dynamic properties in curved laminated glasses - Sukhanova, Olha Ihorivna; Larin, Oleksiy Oleksandrovych (Національний технічний університет "Харківський політехнічний інститут", 2021)
The study presents the results of linear dynamics of laminated glass panels with different curvatures. This is an actual task in the field of mechanical engineering, aviation, shipbuilding, energy, architecture, etc. Such composites are durable, easy to care for and have a wide range of design options. The aim of the work is to study the influence of the curvature parameter on the frequencies and modes of composites. The paper considers the linear characteristics for laminated glass with polyvinyl butyral interlayer. The article considers behavior of the triplex and the propagation of elastic waves in the linear state. The paper performs calculations using the finite element method in the framework of modal analysis in a three-dimensional formulation in the framework of a physical linear-elastic formulation. The study uses hexagonal finite element with 8 nodes with 3 degrees of freedom in each. This work model laminated glass with a curvature parameter ranging from 0 mm to 250 mm. The composite consisted of three layers: two glass layers thickness of each was 3 mm, and a polyvinyl butyral interlayer with 0.38 mm thickness. The size of the plates was 500×500 mm. As a boundary condition, the laminate was fixed on two opposite sides. The article performs mesh size convergence analysis. The results of natural frequencies in accordance with the curvature parameter are derived. The graphs of natural vibration modes are also shown, that give a clear view about the state of composites.

У дослідженні представлені результати лінійної динаміки ламінованих скляних панелей з різною кривизною. Це актуальне завдання у сфері машинобудування, авіаційної промисловості, суднобудування, енергетики, архітектури тощо. Такі композити є довговічними, простими в догляді та мають широкі конструктивні можливості. Метою роботи є вивчення впливу параметра кривизни на частоти та форми компо зитів. У роботі розглядаються лінійні характеристики для ламінованих стекол з полівініл-бутиральним прошарком. Було розглянуто поведінку триплексу та розповсюдження в ньому пружних хвиль у лінійному стані. У даній статті виконано обчислення з використанням методу скінченних елементів в рамках модального аналізу в тривимірній постановці у рамках фізичної лінійно-пружної постановки. Використовувався гексагональний скінченний елемент з 8 вузлами із 3 ступенями волі в кожному. У роботі моделювалися ламіновані стекла з параметром кривизни, що варіювався від 0 мм до 250 мм. Композит складався з трьох шарів: два скляних шара, товщиною 3 мм кожен, та полівініл-бутирального прошарку, товщиною 0,38 мм. Розмір пластин складав 500×500 мм. В якості граничних умов, ламінат був закріплений з двох протилежних сторін. Виконано аналіз збіжності розміру сітки. Виведено результати власних частот в залежності від параметра кривизни. Також показані графіки власних форм коливань, що дають наглядне уявлення про стан композитів.
Keywords: curvature parameter; modal analysis; mesh-size convergence; параметр кривизни; модальний аналіз; збіжність розміру сітки